Effect of thermal annealing conditions on piezoelectric response of ZnO nanorods - Ang, Jia Wen (Nanyang Technological University, 2024)
With particular focus on zinc oxide (ZnO) nanorods to be incorporated into piezoelectric sensors for soft gripper application, this work attempts to investigate the effects of thermal annealing conditions on intrinsic defects and how oxygen vacancies can be manipulated to further improve piezoresponse of the nanorod arrays. Zinc oxide (ZnO) nanorods were prepared on fluorine-doped tin oxide (FTO) glass substrates via a two-step synthesis process to grow oriented nanorod arrays in the (002) preferred orientation. The samples are then subjected to different thermal annealing conditions in a quartz tube furnace. Subsequently, morphology and structure of the prepared samples were characterised using field-emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD). Raman spectroscopy was employed to investigate the presence of oxygen vacancies in the different samples. Piezoelectric properties of the ZnO nanorods were determined via piezoresponse force microscopy (PFM). Obtained results demonstrated that increase in annealing temperature up to 300˚C in oxygen-rich ambient enhanced the piezoelectric and crystalline quality of ZnO nanorod arrays to a larger extent than in oxygen-deficit ambients. Raman spectra also revealed that concentration of oxygen vacancies is significantly reduced by increasing annealing temperature. Based on present findings, to obtain ZnO nanorods with enhanced piezoresponse, optimal annealing condition is oxygen-rich ambient at 300˚C, which is sufficiently high to induce significant improvement in properties and at the same time, sufficiently low to avoid possible substrate degradation.